2020
DOI: 10.1074/jbc.ra120.012684
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional regulator MEIS2 sets up the ground state for palatal osteogenesis in mice

Abstract: Haploinsufficiency of Meis homeobox 2 (MEIS2), encoding a transcriptional regulator, is associated with human cleft palate, and Meis2 inactivation leads to abnormal palate development in mice, implicating MEIS2 functions in palate development. However, its functional mechanisms remain unknown. Here we observed widespread MEIS2 expression in the developing palate in mice. Wnt1Cre-mediated Meis2 inactivation in cranial neural crest cells led to a secondary palate cleft. Importantly, about half of the Wnt1Cre;Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
(68 reference statements)
2
19
0
Order By: Relevance
“…All these three sites share motif -(C/G)CACT(T/C)-, consistent with our Nkx2-5 ChIP-seq results (Ye et al, 2015) and results from another study (He et al, 2011). Our previous studies showed that Shox2 has distinct binding sites among different tissues during organogenesis (Wang et al, 2020;Ye et al, 2016Ye et al, , 2015, but a common motif is yet to be characterized. The binding preferences of Shox2 may be partially dependent upon other co-factors, such as Hox family transcription factors, as reported previously (Ye et al, 2016).…”
Section: An Nkx2-5-dependent Interaction Between Gja5-s1/gja5-s2 and The Gja5 Promotersupporting
confidence: 90%
“…All these three sites share motif -(C/G)CACT(T/C)-, consistent with our Nkx2-5 ChIP-seq results (Ye et al, 2015) and results from another study (He et al, 2011). Our previous studies showed that Shox2 has distinct binding sites among different tissues during organogenesis (Wang et al, 2020;Ye et al, 2016Ye et al, , 2015, but a common motif is yet to be characterized. The binding preferences of Shox2 may be partially dependent upon other co-factors, such as Hox family transcription factors, as reported previously (Ye et al, 2016).…”
Section: An Nkx2-5-dependent Interaction Between Gja5-s1/gja5-s2 and The Gja5 Promotersupporting
confidence: 90%
“…All these three sites share motif -(C/G)CACT(T/C)-, consistent with our Nkx2-5 ChIP-seq results (Ye et al, 2015) and results from another study (He et al, 2011). Our previous studies showed that Shox2 has distinct binding sites among different tissues during organogenesis (Wang et al, 2020;Ye et al, 2016Ye et al, , 2015, but a common motif is yet to be characterized. The binding preferences of Shox2 may be partially dependent upon other co-factors, such as Hox family transcription factors, as reported previously (Ye et al, 2016).…”
Section: An Nkx2-5-dependent Interaction Between Gja5-s1/gja5-s2 and supporting
confidence: 90%
“…Studies on palatal osteogenesis, however, are quite few and limited (Bush & Jiang, 2012). Osteogenesis is a complicated process, but only early osteoblast differentiation is discussed in current studies (Baek et al, 2011; Pauws et al, 2009; Wang et al, 2020; Xu et al, 2018, 2019). In addition, the investigated periods of early osteoblast differentiation differ in multiple publications, making it difficult to understand hard palate development.…”
Section: Introductionmentioning
confidence: 99%